The Effect of Mindfulness Based Intervention on Hiv-Aids Immunity in Adolescents: A Systematic Review - Finta isti kundarti; Ira Titisari; Dwi Estuning Rahayu (Health and Technology Journal (HTechJ), 2025)
Human Immunodeficiency Virus (HIV) is an infection that attacks the body's immune system, especially white blood cells called CD4 cells. Human immunodeficiency virus (HIV) targets the immune system and weakens people's defenses against many infections and some types of cancer. The article was searched through several online databases, including PubMed, ProQuest, Scient Direct, Cochrane Library, and Google Scholar. A total of 8871 articles were obtained that matched the keywords; 259 articles were free of duplication, and 54 full-text articles. Eligibility was carried out to determine articles that met the inclusion criteria, and 10 articles that met the criteria for the age range of respondents were found, with the article being 10-24 years old. The study design used a prospective study and a retrospective study. The total sample was 1,793 HIV-AIDS sufferers. The main result of MBSR is that it can help improve immunity in HIV-infected people. Stress reduction can buffer CD4+ and T lymphocyte decline in diverse community samples of HIV-infected individuals. Mindfulness's positive impact on outcomes is meaningful and important, including improved emotional coping and regulation, increased life satisfaction, decreased aggression, and decreased disease activity.